2014
DOI: 10.2527/jas.2014-8016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fiber digestibility and conservation method on feed intake and the ruminal ecosystem of growing steers1

Abstract: Fiber digestibility is an important factor regulating DMI in ruminants. Additionally, the ensiling process can also affect digestibility and chemical composition of the forage. The objective of this study was to investigate effects of sugarcane NDF digestibility (NDFD) and conservation method on intake, rumen kinetics, and the ruminal ecosystem of steers. Eight ruminally cannulated Nellore steers (275±22 kg BW) were used in a replicated 4×4 Latin square design with a 2×2 factorial arrangement of treatments. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 49 publications
1
16
1
1
Order By: Relevance
“…Moreover, indices of crop quality assume significance: relationship between soluble carbohydrates and gas production (Coblentz et al, 2013), fiber and chemical composition (Jancik et al, 2008), influence of maturity on fiber quality (Palmonari et al, 2014). Eventually, chemical composition of plants influences on nutrition of animals: digestibility of nutrients taking into account fiber from fodder (Sousa et al, 2014), influence of dietary fiber on health (Gidenne, 2015), on ruminal digestion (Brooks et al, 2014). The objective of this work is assessment of chemical composition grain crops taking into account vegetative phases under conditions of steppe are of the South Urals.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, indices of crop quality assume significance: relationship between soluble carbohydrates and gas production (Coblentz et al, 2013), fiber and chemical composition (Jancik et al, 2008), influence of maturity on fiber quality (Palmonari et al, 2014). Eventually, chemical composition of plants influences on nutrition of animals: digestibility of nutrients taking into account fiber from fodder (Sousa et al, 2014), influence of dietary fiber on health (Gidenne, 2015), on ruminal digestion (Brooks et al, 2014). The objective of this work is assessment of chemical composition grain crops taking into account vegetative phases under conditions of steppe are of the South Urals.…”
Section: Introductionmentioning
confidence: 99%
“…For this experiment, samples of rumen contents coming from two previous experiments were used (Mesquita 2013; Sousa et al 2014), which presented the results of performance and ruminal kinetics. The experiments were conducted at the College of Veterinary Medicine and Animal Science, University of São Paulo Beef Cattle Research Laboratory (Pirassununga, SP, Brazil).…”
Section: Methodsmentioning
confidence: 99%
“…In the first experiment (Sousa et al 2014), eight ruminal-cannulated Nellore steers were distributed in two contemporary 4 × 4 Latin Square design. Experimental diets were formulated with 40% sugarcane, either freshly cut or as silage, and 60% concentrate on a DM basis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When silage was included in a corn-soybean meal diet at 40% (DM), Sousa et al (2014) found that cannulated Nellore steers fed the high NDFD sugarcane had higher DMI than cattle fed the low NDFD variety. Oba and Swift (2014) fed two barley silage varieties, Tyto and Falcon, that differed by 4.4% in 30 h NDFD.…”
Section: In Vivo Ndfdmentioning
confidence: 99%